Probing the C iv continuum size-luminosity relation in active galactic nuclei with photometric reverberation mapping - Panda, Swayamtrupta; Pozo Nuñez, Francisco; Bañados, Eduardo; Heidt, Jochen (The astrophysical journal. Part 2, Letters, 2024)
Reverberation mapping accurately determines virial black hole masses only for redshifts z < 0.2 by utilizing the relationship between the Hβ broad-line region (BLR) size and the 5100 Å continuum luminosity established with ∼200 active galactic nuclei. For quasars at z ∼ 2-3 determining the BLR size is time-consuming and limited by seasonal gaps, requiring, e.g., ∼20 yr of monitoring of the C iv emission lines. In this work, we demonstrate that an efficient alternative is to use a continuum size-luminosity relation, which can be obtained up to 150 times faster than BLR sizes using photometric reverberation mapping (PRM). We outline the method and its feasibility based on simulations and propose an observational strategy that can be carried out with meter-class telescopes. In particular, we focus on the ESO La Silla 2.2 m telescope as it is suitable for an efficient PRM campaign. These observations will provide the scaling factor between the accretion disk and the BLR size (for C iv-1350 Å), which is crucial for estimating the masses of black holes at higher redshifts (z ≳ 2-3).
Veröffentlicht: 11. Juni 2024
Gesehen am 22.11.2024